Indoor phthalate exposure and contributions to total intake among pregnant women in the SELMA study. (10th March 2021) - Preece, Anna‐Sofia; Shu, Huan; Knutz, Malin; Krais, Annette M.; Bekö, Gabriel; Bornehag, Carl‐Gustaf
Abstract: Phthalates are widely used in consumer products. Exposure to phthalates can lead to adverse health effects in humans, with early‐life exposure being of particular concern. Phthalate exposure occurs mainly through ingestion, inhalation, and dermal absorption. However, our understanding of the relative importance of different exposure routes is incomplete. This study estimated the intake of five phthalates from the residential indoor environment for 455 Swedish pregnant women in the SELMA study using phthalate mass fraction in indoor dust and compares these to total daily phthalate intakes back‐calculated from phthalate metabolite concentrations in the women's urine. Steady‐state models were used to estimate indoor air phthalate concentrations from dust measurements. Intakes from residential dust and air made meaningful contributions to total daily intakes of more volatile di‐ethyl phthalate (DEP), di‐n‐butyl phthalate (DnBP), and di‐iso‐butyl phthalate (DiBP) (11% of total DEP intake and 28% of total DnBP and DiBP intake combined). Dermal absorption from air was the dominant pathway contributing to the indoor environmental exposure. Residential exposure to less volatile phthalates made minor contributions to total intake. These results suggest that reducing the presence of low molecular weight phthalates in the residential indoor environment can meaningfully reduce phthalate intake among pregnant women.